DAMPAK PUTUSAN MAHKAMAH KONSTITUSI NOMOR 35/PUU-X/2012 ATAS HUTAN ADAT SEBAGAI ASSET NAGARI DI PROPINSI SUMATERA BARAT - Erry Gusman (Ensiklopedia Sosial Review, 2022)
In the laws and regulations in Indonesia, ulayat rights are recognized, respected and protected, meaning that the existence/existence of ulayat rights is recognized and protected from all actions that interfere with ulayat rights by anyone, the various kinds of legislation are: First, the Constitution 1945 in article 18 B paragraph (2) contains provisions regarding the recognition and respect for ulayat rights. Second, Article 6 of the MPR Decree No. IX/MPR/2011 on “Agrarian Reform and Natural Resource Management”. Third, Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles. And the fourth is Law Number 39 of 1999 concerning Human Rights. In addition to the laws and regulations that acknowledge the existence/existence of ulayat rights, there are also denials of ulayat rights in statutory regulations. These laws include: Law Number 5 of 1967 concerning Provisions on Basic Provisions of Forestry, this law was revoked by Law Number 41 of 1999 concerning Forestry. Law Number 41 of 1999 states customary forests as state forests, so that the state can give the forest to a legal subject with a right. This means the denial of the rights of the customary law community to their customary forest and it also means the denial of the customary law community's customary rights. With the issuance of the Constitutional Court's decision No. 35/PUU-X/2012 regarding the review of Law no. 41 of 1999 concerning Forestry, brought fresh air to customary law communities, where in its decision the Constitutional Court has emphasized the existence of customary forests so that the legal certainty of the existence of customary forests is really strong.Keywords: Decision, Constitutional Court, Customary Forest, Nagari, West Sumatra.